199k views
5 votes
Rearrange
X=2w + 1 over 5 – 3w
to make w the subject.
(4 marks)
W =

User Clweeks
by
6.2k points

1 Answer

2 votes

Answer:

Rearranging the expression
x=(2w+1)/(5-3w) to make w the subject we get
\mathbf{w=(1-5x)/(-3x-2) }

Explanation:

We need to rearrange the expression
x=(2w+1)/(5-3w) to make w the subject.


x=(2w+1)/(5-3w)\\x(5-3w)=2w+1\\5x-3wx=2w+1\\

Subtract 2w on both sides


5x-3wx-2w=2w+1=2w\\5x-3wx-2w=1\\

Subtract 5x on both sides


5x-3wx-2w-5x=1-5x\\-3wx-2w=1-5x\\

Taking w common on left hand side


w(-3x-2)=1-5x\\

Divide both sides by -3x-2


(w(-3x-2))/(-3x-2) =(1-5x)/(-3x-2)\\w=(1-5x)/(-3x-2)

So, rearranging the expression
x=(2w+1)/(5-3w) to make w the subject we get
\mathbf{w=(1-5x)/(-3x-2) }

User McNets
by
6.2k points